In search of the African voice in higher education: The language question - Kaschula, Russell (Stellenbosch Papers in Linguistics Plus, 2016)
This article seeks to understand what South African universities are doing by making use of language as a tool or as an enabling voice towards Africanisation and transformation with particular reference to Rhodes University, which serves as a case study. Although many universities now have language policies in place and are part of an enabling policy environment, when it comes to using language as part of transformation and asserting an African voice, there are still policy implementation challenges. It is argued in this article that implementation of policy, including university language policies, is now a key indicator for two levels of transformation; namely the more superficially visible or visual representation transformation, as well as deeper curriculum transformation through appropriate language usage. It is the latter form of transformation that largely eludes the contemporary South African university, whether these are historically black universities (HBUs) or historically white universities (HWUs). With the exception of a few best practices that are highlighted in this article, it is argued that transformation of the curriculum remains a long-term process, in the same way that language policy implementation is an ongoing process and requires commitment at all levels of university managerial and academic culture. The African voice in higher education remains an elusive one; though it is gaining ground, as evidenced by the recent removal of the Cecil John Rhodes Statue at the University of Cape Town. Furthermore, there is evidence of selected ongoing curriculum and pedagogic transformation, as presented in this article.